Addressing the Causes and Effects of Climate Change in Afghanistan: Mitigation Strategies and Solutions for a Sustainable Future - Stanikzai, Irfan Ullah; Hamdard, Wasiq Ullah; Sereet, Abdul Hameed; Aryan, Fawad (International Journal of Environment, Engineering and Education, 2024)
The goal of this research is to address the causes and effects of climate change in Afghanistan and to develop strategies and solutions for a sustainable future. A qualitative approach was utilized, employing semi-structured interviews with climate change experts selected via snowball sampling. These interviews were audio-recorded, transcribed, coded, and analyzed through thematic analysis. The study identified various causes of climate change in Afghanistan, such as deforestation, fossil fuel combustion, urbanization, ongoing conflicts, industrial activities, inefficient waste management, and poor water management practices. These factors have culminated in escalating droughts, melting glaciers and snow, floods and storms, as well as adverse effects on agriculture and livestock, and an increase in diseases among humans, animals, and plants. The research underscores the urgent need for mitigation strategies and sustainable solutions for Afghanistan’s future. Proposed strategies and solutions include seeking foreign aid, collaborating with national and international organizations, raising public awareness, preventing deforestation and smuggling, implementing water storage measures, learning from other countries’ experiences, conducting further assessments and research, expanding greenery, and formulating comprehensive policies and strategic plans for water management. The findings are significant for the Afghan government, national and international organizations engaged in climate change efforts, and policymakers. Given Afghanistan's heightened vulnerability to climate change, it is essential to take proactive measures and prioritize mitigation and adaptation efforts to ensure a sustainable future for the country. Addressing these critical issues will require coordinated action and sustained commitment from all stakeholders involved.